Kajian Terhadap Kepuasan Pemustaka dalam Menerima Layanan Petugas Perpustakaan di Perpustakaan Universitas Negeri Jakarta - Ahmad Rijal Pahlevy; Thamrin Hasan (Jurnal Gema Pustakawan, 2021)
User satisfaction is important in determining the growth and progress of the library. Users who feel satisfaction with library services tend to feel happy. Conversely, those who do not feel satisfied tend to feel displeased. Feelings of pleasure and displeasure are perceptions that are relative. Empirically the symptoms of perception of feeling happy and not happy with the service can be seen. This is a serious concern and a question that must be answered, how is the level of user satisfaction with the services of officers at the Jakarta State University library. The purpose of the study was to determine the level of user satisfaction with the services of the Jakarta State University librarian. The study uses a descriptive method. The sample studied was 350 respondents. The sampling technique was carried out by accidental sampling. The research instrument used a questionnaire with a Likert scale model. The data analysis technique used descriptive statistical analysis. The results of the research as a whole indicate that the satisfaction of users with the services of librarian is included in the satisfactory category. It can be shown that the total average score generated is 3.70. The results of this study are useful for determining strategies in improving the performance of library services. The conclusion of the study shows that the users are satisfied with the services of the librarian. This means that the service performance of the librarian can provide satisfaction. Keywords: satisfaction; user; performance; and libraries.